IMPLEMENTASI PROGRAM KEWIRAUSAHAAN DALAM MENGURANGI KEMISKINAN DI KOTA BATAM - Dompak, Timbul; Assyafaah, Nur (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
This study looks at how Batam City's poverty can be reduced through the implementation of MSME program development. According to BPS Batam City data, the proportion of the population living in poverty fell from 5.19% in 2022 to 5.02% in 2023. MSMEs seek to lower the rate of poverty. This study takes qualitative research using a literature study approach. Researchers use secondary data from sources such as books, papers, journals, notes, statistical data, previous research, and documents. The findings demonstrated that MSMEs contribute to poverty alleviation by creating new job possibilities, particularly in the small and medium industrial sector, which employs a significant number of people. In order to have a greater influence on decreasing poverty, the Batam City Government continues to promote the growth of MSMEs and the enhancement of community welfare through a number of initiatives, such as the granting of financial incentives and the distribution of economic aid. However, MSMEs encounter numerous issues during implementation that require careful consideration and management. These issues include capital problems brought on by limited collateral that makes it difficult to obtain financial institutions and lack of access to market data, which hinders marketing. in the process of obtaining a company license.